2019
DOI: 10.1186/s13613-019-0583-y
|View full text |Cite
|
Sign up to set email alerts
|

Morpho-functional evaluation of lung aeration as a marker of sickle-cell acute chest syndrome severity in the ICU: a prospective cohort study

Abstract: BackgroundAcute chest syndrome (ACS) is the main cause of morbi-mortality in patients with sickle-cell disease in the intensive care unit (ICU). ACS definition encompasses many types of lung damage, making early detection of the most severe forms challenging. We aimed to describe ACS-related lung ultrasound (LU) patterns and determine LU performance to assess ACS outcome.ResultsWe performed a prospective cohort study including 56 ICU patients hospitalized for ACS in a tertiary university hospital (Paris, Franc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…When RBC transfusion was considered during a VOE, but the indication is not clear-cut (in clinical practice, when the interpretability of the child-reported pain score is difficult), then the analysis of leukocyte count and CRP level at day 2 may help in a decision. Interestingly, a recent study performed in adult patients with severe ACS hospitalized in intensive care unit, comparing ACS-related lung ultrasound patterns at admission and after 48 h reported that the evolution of lung aeration during the first two days was strongly associated with outcome events occurring beyond this time point [34]. Early detection of patients who will experience a complicated outcome during VOE and ACS is a major concern, since it would allow physicians to modify their management accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…When RBC transfusion was considered during a VOE, but the indication is not clear-cut (in clinical practice, when the interpretability of the child-reported pain score is difficult), then the analysis of leukocyte count and CRP level at day 2 may help in a decision. Interestingly, a recent study performed in adult patients with severe ACS hospitalized in intensive care unit, comparing ACS-related lung ultrasound patterns at admission and after 48 h reported that the evolution of lung aeration during the first two days was strongly associated with outcome events occurring beyond this time point [34]. Early detection of patients who will experience a complicated outcome during VOE and ACS is a major concern, since it would allow physicians to modify their management accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we report for the first time an association between sputum IL‐6 level measured within the first days of hospitalisation for ACS and ACS severity. ACS is one of the most severe acute complications of SCD with high morbimortality and prolonged hospitalisation length 1,2,10 . To date, very few studies have tried to identify early markers of ACS severity 4,11 .…”
Section: Resultsmentioning
confidence: 99%
“…ACS is one of the most severe acute complications of SCD with high morbimortality and prolonged hospitalisation length. 1,2,10 To date, very few studies have tried to identify early markers of ACS severity. 4,11 Plasma levels of secretory phospholipase A2 were found associated with hypoxia during ACS, but investigations regarding this inflammatory mediator as a potential marker of ACS severity have not been conducted further.…”
Section: Sputum Il-6 Levels Are Significantly Higher In Patients With...mentioning
confidence: 99%
“…In SCD patients, occlusion of the small blood vessels presents as episodes of severe pains that called vasoocclusive crisis (VOC), which damage to the vital organs. Some patients develop acute chest syndrome (ACS), a major cause of death in SCD (132). iNO has positive effect in the pathophysiological and therapeutic in case series of ACS patients (133).…”
Section: Sickle Cell Disease (Scd)mentioning
confidence: 99%